THE ROLE OF URBAN GREEN SPACES IN CLIMATE ADAPTATION OF SOUTHEAST ASIAN TROPICAL CITIES - Mohamed, Ahmed; Ibrahim, Fatima; Said, Amina (Journal of Selvicoltura Asean, 2026)
Rapid urbanization in Southeast Asian tropical cities has intensified vulnerability to climate-related hazards, including urban heat islands, flooding, and reduced air quality. Limited green infrastructure exacerbates these challenges, while urban green spaces such as parks, gardens, and tree-lined streets offer potential mitigation by enhancing microclimate regulation, stormwater management, and social well-being. Despite recognition of their importance, the role of urban green spaces in climate adaptation remains insufficiently quantified and integrated into city planning. This study aims to evaluate the effectiveness of urban green spaces in supporting climate adaptation strategies in Southeast Asian tropical cities. The research focuses on their ecological, social, and infrastructural contributions to reducing urban vulnerability and enhancing resilience to climate stressors. A mixed-methods approach was employed, combining geospatial analysis of land cover and green space distribution, secondary climate and socio-economic data, and surveys of 300 residents across three major cities. Quantitative data were analyzed using statistical modeling to examine relationships between green space coverage and urban climate indicators, while qualitative data provided insights into community perceptions and adaptive practices. Results indicate that increased green space coverage correlates with reduced surface temperatures, improved stormwater absorption, and enhanced community awareness of climate risks. Residents reported higher well-being and perceived safety in areas with accessible green infrastructure. The study concludes that urban green spaces are essential components of climate adaptation strategies in tropical cities, offering co-benefits for ecology, social resilience, and infrastructure planning.